A Novel c.968C > T homozygous Mutation in the Polynucleotide Kinase 3′ − Phosphatase Gene Related to the Syndrome of Microcephaly, Seizures, and Developmental Delay - Marcilla Vázquez, Carlos; Carrascosa Romero, María del Carmen; Martínez Gutiérrez, Andrés; Baquero Cano, María; Alfaro Ponce, Blanca; Dabad Moreno, María Jesús (Journal of Pediatric Genetics, 2020)
Microcephaly is defined by a head circumference that is at least two standard deviations below the mean for age and sex of the general population in a specific race. Primary microcephaly may occur as an isolated inborn error, which may damage to the central nervous system or as part of the congenital abnormalities associated with genetic syndrome, affecting multiple organ systems. One of the syndromic forms consists of microcephaly, seizures, and developmental delay caused by biallelic mutations in the gene that encode polynucleotide kinase 3′ − phosphatase protein (PNKP). In this article, we reported a newborn male who presented with microcephaly, severe developmental delay, and early-onset refractories seizures, caused by a novel homozygous mutation of the PNKP gene.
Keywords: polynucleotide kinase 3′ − phosphatase; microcephaly; seizure